Biomechanical characteristics of the Axe kick in Tae Kwon-Do - Yu, D.; Yu, Y.; Shan, G.; Wilde, B. (Archives of Budo, 2012)
Background and Study Aim: In the current literature, few scientific studies can be found related to the biomechanical characterization of the Axe Kick - one powerful Tae Kwon-Do kick. This study aimed to supply the kinematics of an effective axe kick by quantifying the skill using 3D motion capture technology and full body biomechanical modelling. Material and Methods: A 3D motion-capture system with four camcorders (60 frames/s, SIMI motion 7.3) was used to measure full-body movement of 12 subjects (4 professionals & 8 advanced fighters). The measured data was used to build 14 segmental biomechanical modelling for obtaining parameters such as coordinates, ranges of motion and speeds of joints. Statistical T-tests were used to determine the kinematic differences between the two groups in order to quantify the effective way for conducting the skill. Results: There are significant differences existing in the flexibility of hip, knee control of the kicking leg as well as time used for lifting and downward drive of the foot. These differences may be used to account for the 15% difference observed in action time, 12% in maximal kick height and 20% in maximal drive speed of the kick foot between professional and advanced fighters. Conclusions: An axe kick can be characterized as a whip-like kicking movement during leg lift and an axe-like movement during the downward drive of the heel. Hip flexibility, muscle power and whip-like movement are keys to the kick quality.